2015
DOI: 10.1007/s10029-015-1350-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized clinical trial of Jean Rives technique versus laparoscopic TEP repair for primary inguinal hernia: 10-year follow-up

Abstract: Jean Rives technique is a relatively easy technique to perform, requires shorter operating time when compared to laparoscopic TEP technique. JR technique should be taken into consideration while planning surgical treatment of inguinal hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Sixty‐seven studies met the inclusion criteria. Nine studies had the same participants with different durations of follow‐up, resulting in 58 RCTs with unique populations ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty‐seven studies met the inclusion criteria. Nine studies had the same participants with different durations of follow‐up, resulting in 58 RCTs with unique populations ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies (36 per cent) reported pain as an outcome after 1 year, with 4481 patients randomized in the open repair group and 4290 in the laparoscopic repair group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these data, realistic recurrence rates can be calculated after surgical repair of inguinal and incisional hernia. This is useful since the majority of published studies on hernia surgery only have a follow-up period of 1–5 years (2), and studies with a 10-year follow-up are an absolute exception (37). As a consequence of our own data, we will extend the follow-up of the patients with inguinal hernia repair in the Herniamed Registry to a minimum of 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that recurrence continues to occur after the follow-up period of 1–5 years usually used in most hernia studies (2). There are relatively few studies that have calculated the recurrence rates following inguinal and incisional hernia operations after a follow-up of 10 years (37). To date, there are no studies on recurrences after a follow-up of more than 10 years.…”
Section: Introductionmentioning
confidence: 99%